2015
DOI: 10.1017/sjp.2015.73
|View full text |Cite
|
Sign up to set email alerts
|

The Thousand Shades of the Financial and Economic Crisis: a Study of the Social Representations of the Crisis in Portugal

Abstract: The study describes the representations of 453 Portuguese students about the present financial and economic crisis, examining the impact of the family financial situation on these representations, and the relationship between these representations and different factors likely to influence them. An initial word association task produced 2339 responses, from which 86.75% were classified into six classes by a downward hierarchical classification. Four classes (58.26% of the corpus) confirmed that the austerity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Others have examined the effect of people's financial position, feelings of vulnerability, and emotions on their willingness to take action against the austerity measures implemented in their country (Chryssochoou, Papastamou & Prodromitis, 2013;Poeschl, Valentim & Silva, 2015).…”
Section: Lay Theories About the Economic Crisismentioning
confidence: 99%
“…Others have examined the effect of people's financial position, feelings of vulnerability, and emotions on their willingness to take action against the austerity measures implemented in their country (Chryssochoou, Papastamou & Prodromitis, 2013;Poeschl, Valentim & Silva, 2015).…”
Section: Lay Theories About the Economic Crisismentioning
confidence: 99%
“…Respondents with a lower family income experienced less positive emotions and more negative emotions toward the crisis, as well as stronger feelings of vulnerability and relative deprivation that resulted from comparison with others (Poeschl, Valentim, & Silva, 2015). However, respondents did not differ in their expectations about their future situation, which they foresaw without great changes, and, unlike the Greek respondents, declared a similar unwillingness as the other respondents to participate in protest actions.…”
Section: Lay People's Representations Of the Economic Crisismentioning
confidence: 79%
“…Another study using a free association task compared the discourses of Portuguese students based on their family income (Poeschl, Valentim, & Silva, 2015). The word most frequently associated with the crisis was "poverty".…”
Section: Lay People's Representations Of the Economic Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies on the social representations of crisis (Galli et al, 2010;Poeschl, Valentim & Silva, 2015), showed that crisis is perceived mostly through negative meanings, like poverty, unemployment, and (lack of) money. But the understanding of crisis is anchored in differences in the people's financial situation.…”
Section: Studying Lay Knowledge Of Economic Crisis: the Social Represmentioning
confidence: 99%